Hubungan antara Dukungan Sosial Rekan Kerja dan Komitmen Karier pada Guru SMA Swasta Umum Binaan DISDIKPORA Kota Salatiga - Ariani, Dwi Setya; Wijono, Sutarto; Setiawan, Adi (Noetic Psychology, 2014)
AbstractÃÂ The purpose of this research is to verify the correlation between Coworker Support and Career Commitment. There are two scales used in this research, i.e. Coworker Support Scale by Lane (2004) and Career Commitment Scale by Carson & Bedeian (1994). The participants of this research are 60 teachers of private high-school in Salatiga, Indonesia. Data analysis uses SPSS 16 Program. StatisticÃ¢â¬â¢s method to be used is pearson product moment correlation test. The result of statistic test shows that there is significant correlation between Coworker Support and Career Commitment.ÃÂ Key words: Coworker Support, Career Commitment, teachers at private high-school in Salatiga, Indonesia.